Theoretical study of the charge transfer and electron emission in the scattering of He+ by an AlF3 surface - Iglesias Garcia, Adalberto de Jesus (2017)
Experimental results of electron emission from surfaces of aluminum fluoride impacted by keV noble gas ions (He+, Ne+, Ar+) show a high-energy structure that increases in intensity with ion energy in the case of He+ and Ar+ and is nearly independent on the impact energy for Ne+ ions. It is also observed that this high-energy secondary electron peak is less pronounced in the case of impact by Ar+. While ion-induced electron emission in metal surfaces is relatively well understood, in the case of wide band-gap insulators, such as metal fluorides, the nature of high-energy excitations is still an open question. In this work, we propose a mechanism of high-energy electron emission strongly linked to the ion neutralization process and the collision induced excitation of the electrons in the solid.